#### Answer

$-7$

#### Work Step by Step

Recall the following rule:
$(a^{b})^{c}=a^{bc}$
Thus, we obtain:
$-\sqrt {49}=-\sqrt {7^{2}}=-(7^{2})^{\frac{1}{2}}=-7^{1}=-7$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

$-7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.